NOVEL NOVEL STABILITY-INDICATING HIGH-PERFORMANCE LIQUID CHROMATOGRAPHIC ASSAY METHOD FOR SIMULTANEOUS ESTIMATION OF HYDROCORTISONE AND TETRACYCLINE IN BULK AND PHARMACEUTICAL DOSAGE FORM - MUNI SAI VARAGANTI; PRASANTHI CHENGALVA; ARUNA GUNDALA (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: A combination of hydrocortisone and tetracycline as topical ophthalmic ointment is used for skin irritations, eye infections, inflammation, skin infections, acne, and rashes. The objective of the current work is to a simple, rapid, accurate, and precise, stability-indicating reverse-phase liquid chromatographic method was developed for the simultaneous estimation of hydrocortisone and tetracycline in bulk and pharmaceutical dosage form. Methods: The separation was carried out in Discovery C18 column (250 × 4.6 mm, 5 μm) using mobile phase ratio of water (pH 2.2 adjusted with orthophosphoric acid):acetonitrile (40:60 v/v) in an isocratic elution mode with a flow rate of 1.0 ml/min at detection wavelength of 244 nm. The injection volume was 10 μl and the column temperature was set at 30°C. Results: The retention time for hydrocortisone and tetracycline was found to be 2.214 ± 0.001 min and 3.497 ± 0.001 min, respectively. Calibration curves were linear (r2=0.999) at a concentration range of 2.5–15 mg/ml for both hydrocortisone and tetracycline. The percentage recoveries were found to be 99.13–99.67% for hydrocortisone and 99.39–99.61% for tetracycline. Relative standard deviation was found to be 0.3% for both the drugs. Limit of detection and limit of quantification values of hydrocortisone and tetracycline were found to be 0.09 μg/ml and 0.27 μg/ml and 0.17 μg/ml and 0.52 μg/ml, respectively. The drugs were subjected to various stress conditions and found no interference of degraded products peak at the retention times of analyte peaks. Conclusion: A rapid and accurate reverse-phase high-performance liquid chromatographic method was developed for simultaneous estimation of hydrocortisone and tetracycline, and the method was validated as per the International Council for Harmonization guidelines. Hence, the developed method can be successfully applied for the simultaneous estimation of hydrocortisone and tetracycline in bulk and ointment formulation.